Comparacion entre el regimen simple de tributacion y el regimen ordinario bajo la ley 2277del 2022 (2023)
Based on the knowlendge we acquired in the Public Accounting undergraduate program and our responsibility to comply with tax regulations, we conducted a comparison of the simplified tax regime and the ordinary tax regime. Using a documentary and comparative methodology, with a qualitative approach, we collected and analyzed information on the regulations, governing each regime. The analysis revealed that the two regimes are companies with income higher that those companies that qualify for the simplified regime. Additionally, the ordinary regime permits deducting costs and expenses directly related to economic activity, While the simple regime cannot make this deduction. Both regimes are necessary for effective taxation in Colombia, but because each regime has its advantage and disadvantages, it is important to conduct a thorough analysis before choosing one of them